2019
DOI: 10.1097/wad.0000000000000359
|View full text |Cite
|
Sign up to set email alerts
|

Translation and Validation of 10/66 Dementia Diagnostic Battery in Urdu in Karachi, Pakistan

Abstract: Purpose: The 10/66 dementia research group (DRG) diagnostic tool was devised to diagnose dementia in people with low education in low and middle-income countries. This study aimed to validate the 10/66 DRG tool in Urdu in Pakistan. Methodology: People older than or equal to 60 years were included: (1) With normal cognition: no/low education, high education, and depression; (2) People with mild and moderate dementia. The diagnostic and statistical manual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Although our sample size was relatively small, we have demonstrated that the translated and adapted Fijian-Indian version of the 10/66 dementia protocol has adequate sensitivity (92.3%, 95% CI 70.3–99.5) and specificity (93.8%, 95% CI 75.3–99.6), PPV (92.3%), NPV (93.8%), and a Youden’s index of 0.86. We are confident that the Fijian-Indian version of the 10/66 dementia protocol would have similar utility as other versions of 10/66 dementia protocols [ 20 , 21 , 22 ]. To date, the actual extent and impact of dementia in the Fijian-Indian population is unknown.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Although our sample size was relatively small, we have demonstrated that the translated and adapted Fijian-Indian version of the 10/66 dementia protocol has adequate sensitivity (92.3%, 95% CI 70.3–99.5) and specificity (93.8%, 95% CI 75.3–99.6), PPV (92.3%), NPV (93.8%), and a Youden’s index of 0.86. We are confident that the Fijian-Indian version of the 10/66 dementia protocol would have similar utility as other versions of 10/66 dementia protocols [ 20 , 21 , 22 ]. To date, the actual extent and impact of dementia in the Fijian-Indian population is unknown.…”
Section: Discussionmentioning
confidence: 91%
“…We used the clinical diagnosis as a reference standard for memory service-based participants, which is accepted and used as the reference standard in clinical dementia studies worldwide [ 20 , 21 , 22 ]. Its validity has been previously demonstrated in multiple studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the 10/66 dementia research group (DRG) diagnostic tool was formulated and validated in various LMICs 2. A pilot study was conducted in Karachi, Pakistan by our group that used 10/66 methodology to validate the 10/66 DRG diagnostic tool in Urdu 3. The 10/66 DRG diagnostic battery not only takes 2 to 3 hours for testing, but also requires specialized and longer training for the data collectors to administer the battery.…”
mentioning
confidence: 99%